(untitled) (Innovaciones Educativas, 2022)
Higher education is facing a methodological update due to the changes caused by the health crisis generated by the virus responsible for COVID-19; consequently, the Division of Education for Work at Universidad Nacional seeks to analyze the context and the pedagogical mediation arising since 2020 from the student and teacher perspective. Three core elements are analyzed within the framework of a naturalistic paradigm from an exploratory methodology to identify the advantages and disadvantages of working in a remote face-to-face modality, as well as the possible adjustments to be made in an eventual face-to-face return and the modality preference of the participants in this training process. Regarding these three main results, advantages are highlighted, indicated by both the students and the teaching staff, which are presented at a personal, family, economic, quality of life, and health level, in addition to academic aspects, such as the development of skills, capacities for professional life and for the continuity of vocational projects, among others. The disadvantages refer to household activities, multitasking, ergonomic conditions, social interaction, and connectivity. In addition, within the eventual adjustments, we have: working conditions, the ability to adapt to change, scheduled organization, and the economic situation. The study concludes that the impact of the virus responsible for Covid-19, in the medium-to-long term, in university life is inevitable, and its scope will affect the institutional organization, teaching practices, and bonding between the ones involved.